ARGEMmy: An intermediate DSGE model calibrated/estimated for Argentina: two policy rules are often better than one - Guillermo Escudé (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2009)
The purpose of this paper is to advance in the construction and calibration/estimation of an intermediate DSGE model with two policy rules for Argentina and explore to what extent two policy rules can be better than one. The BCRAs research department currently uses a very small and non-micro founded model with two policy rules which I designed a few years ago (MEP: Modelo Económico Peque\~no (see Elosegui, Escudé, Garegnani and Sotes Paladino 2007)) as the backbone for a system of macro and monetary projections. During 2006-07 I constructed the much larger DSGE model ARGEM, mainly for research purposes. It seemed that there was need for an intermediate sized DSGE model that could be of help in bridging the gap between the two. ARGEMmy is the result of this new effort. Hopefully, it will help in bringing the DSGE modeling strategy closer to the policy environment.
Keywords: C32; C63; 330; Argentina; Bayesian estimation; DSGE models; policy rules